Philosophy of Tradition (Journal of Philosophy Culture and Political Science, 2019)
Philosophical foundation of tradition is discussed in this article. Updating the problems of traditional culture in the modern world appears as response to globalization and the need for constant renewal of the cultural heritage of the people. Tradition here is a large-scale form of organization of social and spiritual life, which has a greater stability over time and space, based on the universal connection of individuals and groups through the material and spiritual aspects. Spiritual forms of social interactions have universal signiﬁ cance and implemented in the necessary structural components, also these forms acquire a special signiﬁ cance. Social carriers of this tradition provide its integrity, which is the unity of spiritual values, ideas, knowledge, orientation, norms and symbols. The unity of tradition and innovation ensures the continuity in the development of society and its relationship with the future, also it dominates the dynamics of its society, which manifests itself in different periods of formation and development of ethnic. Tradition and innovation are an open system, which does not have deﬁ ned hard limits, and are capable of self-reproduction and self-regulation. Its socio-cultural, epistemological, ontological and axiological parameters have particular importance.